Study of Electrical Energy Consumption in the East of Thailand with Cluster Analysis - เมฆพายัพ Chatuphat; Saithanu, Kidakan; Phodjanawichaikul, Phodjana (Journal of Advanced Development in Engineering and Science, 2023)
This research was to group the electrical energy consumption of total seven eastern provinces in the East of Thailand with cluster analysis. The consumption was collected from 2008 to 2017 National Statistical Office of Thailand, Ministry of Information and Communication Technology. The results of this research illustrated that cluster analysis was able to divide the electrical energy consumption of all provinces in the East of Thailand into three clusters. The first cluster consisted of three provinces, Chonburi, Rayong and Chachoengsao with high electrical energy consumption. The second cluster was moderate electrical energy consumption (Prachinburi). The third cluster was low electrical energy consumption in association with three provinces, Chanthaburi, Sakeo and Trat. Moreover, cluster analysis also discriminated periods of the electrical energy consumption into three groups. The first cluster was the high period of the electrical energy consumption (2016 to 2017), the second cluster was the moderate period of the electrical energy consumption (2011 to 2015) and the third cluster was the low period of the electrical energy consumption (2008 to 2010).